Infant motor development - Piek, Jan P. (Human Kinetics, 2006)
Text is organized into four parts covering theory, research, assessment, and intervention. It integrates information from a variety of disciplines to encourage a broad understanding of infant motor development. Topics include the development of voluntary movements such as posture, stability, balance, and orientation; manual control of reaching and grasping; locomotor control of creeping and walking; the unique difficulties faced by premature infants; and an examination of two disabilities with devastating consequences to motor control: cerebral palsy and Down syndrome